THE BIOPHARMACEUTICAL INVESTIGATION OF PARACETAMOL SUPPOSITORIES FROM DOMESTIC MANUFACTURERS - T. V. Orlova; T. A. Pankrusheva; N. D. Ogneschikova; A. V. Nesterova (Разработка и регистрация лекарственных средств)
The quality of Paracetamol suppositories produced by domestic manufacturers has been investigated and their compliance with pharmacopoeial requirements has been established. Dissolution profile test of paracetamol suppositories of different producers has been carried out and nonequivalence of profiles due to the properties of the suppository basis has been shown. The importance of hydroxyl value and melting point of fat suppository bases used as pharmaceutical factors has been highlighted.